MSS417 - Coding Theory February 2021 - PPSM, Pusat Pengajian Sains Matematik (Universiti Sains Malaysia, 2021)
1. You must be on webcam and Microsoft Team all the time before downloading the examination paper till I confirmed all answer scripts have been received in USM E-learn. 2. Please check that the examination paper consists of THREE (3) pages of printed material with THREE (3) questions. 3. DO NOT start to answer until 3.45pm of 19th Feb 2021. 4. All the answer scripts need to be submitted in PDF format. 5. On the first page of each answer script write the date and time of the exam; exam id (angka giliran) in digits and words; code and name of the subject. 6. On the top of each page of written answer need to write the exam id in digit form and the question number. 7. Complete answer script needs to be fully uploaded before or by 6.30pm of 19th Feb 2021. 8. Any submission after 6.30pm of 19th Feb 2021 will not be entertained. 9. No appeals for incorrect files or incomplete answer scripts will be entertained after 6.30pm of 19th Feb 2021. 10. If you face any problem in uploading any answer script to E-learn, you must inform me before 6.10pm to arrange for other alternative submission platforms.